2020
DOI: 10.1111/iwj.13436
|View full text |Cite
|
Sign up to set email alerts
|

The effect of transcutaneous application of gaseous CO2 on diabetic chronic wound healing—A double‐blind randomized clinical trial

Abstract: Chronic wounds in diabetics are difficult to treat, therefore, adjuvant therapies have been investigated. Bathing in CO2‐rich water (spa therapy) has been known in Europe for decades for its positive effect on peripheral vascular disorders. Recently, much effort has been invested in developing optimal application methods of CO2. Uses include subcutaneous injections of CO2, bathing in CO2‐enriched water, and transcutaneous application of CO2. To verify the effect of transcutaneous application of gaseous CO2 on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Macura et al 33 measured the area and volume of the wound (induced by either ischemia or neuropathy or a combination) before and after therapy while also assessing the wound bed. They found that 20 (approximately 67%) wounds receiving carboxytherapy healed utterly, while all three mentioned parameters improved significantly in the remaining ones ( p ‐value = 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Macura et al 33 measured the area and volume of the wound (induced by either ischemia or neuropathy or a combination) before and after therapy while also assessing the wound bed. They found that 20 (approximately 67%) wounds receiving carboxytherapy healed utterly, while all three mentioned parameters improved significantly in the remaining ones ( p ‐value = 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Carboxytherapy is a well-known technique in dermatology, and it has been used for several years for both aesthetic and pathological conditions [3][4][5][6]. It is considered a simple and safe procedure, with mostly mild and temporary adverse events such as pain and bruising [5].…”
Section: Discussionmentioning
confidence: 99%
“…[100][101][102][103][104][105][106][107][108][109] In addition, we found one study on nitric oxide, 110 three on ozone therapy, [111][112][113] two on cold atmospheric plasma 114,115 , and one on carbon dioxide. 116 With all of these studies being either at high risk of bias and/or with lack of demonstrable effect, these were grouped together as 'other gases'. Rationale: Of the 18 studies on the evaluation of the use of hyperbaric oxygen as an adjunct therapy to improve diabetes-related foot ulcer healing, only three were double-blinded RCTs.…”
Section: Intervention: Oxygen and Other Gasesmentioning
confidence: 99%